KORELASI FAKTOR PENGARUH PERILAKU MENGEMBANG TANAH TERHADAP NILAI SWELLING PRESSURE - Tuhumury, Joan Nathasya; Iskandar, Ali (JMTS: Jurnal Mitra Teknik Sipil, 2025)
There are numerous challenges faced by geotechnical engineers in ensuring the construction of safe and durable infrastructure, one of which is the presence of expansive soils. Expansive soil refers to any soil or rock material that has the potential to shrink or swell due to changes in moisture conditions. However, moisture content is not the only factor affecting soil expansion behavior; Plastic limit, Liquid limit, Plasticity Index, Clay Percentage and Fine Content Percentage also play significant roles.Under certain conditions, these parameters may not directly influence the degree of soil expansion. These parameters significantly impact soil swelling when expansive minerals like montmorillonite or vermiculite are present. In this study, while X-Ray Diffraction Analysis was not conducted to identify soil minerals, the coefficients of determination indicate that dry density, water content, natural void ratio, initial void ratio, and fine content percentage are the most influential factors affecting swelling pressure, respectively. However, variations in samples may lead to differing conclusions due to the lack of information regarding the mineral composition of each sample. Abstrak Terdapat banyak tantangan bagi insinyur geoteknik dalam pelaksanaan pembangunan infrastruktur yang aman dan tahan lama, salah satunya adalah keberadaan tanah ekspansif. Tanah ekspansif adalah istilah yang diterapkan pada material tanah atau batuan apa pun yang berpotensi menyusut atau membengkak karena kondisi kelembapan yang berubah. Namun tidak hanya kelembaban yang memengaruhi perilaku mengembang tanah, rasio pori tanah, Plastic limit, Liquid limit, Plasticity Index, Clay Percentage, dan Fine Content Percentage juga memengaruhinya. Pada kondisi tertentu beberapa parameter ini tidak semata mata memengaruhi besarnya pengembangan tanah. Parameter-parameter tersebut akan berpengaruh secara signifikan apabila diiringi dengan kondisi tanah lempung yang mengandung mineral ekspansif seperti montmorillonite atau vermiculite. Pada penelitian ini tidak dilakukan X-Ray Diffraction Analysis sehingga tidak ada data mengenai mineral yang terkandung dalam sampel tanah, namun dari nilai masing-masing koefisien determinasi dapat disimpulkan bahwa secara berurutan, dry density, water content, natural void ratio, initial void ratio, dan %fine content adalah yang paling memengaruhi nilai swelling pressure.